Red-Free Fundus Photograph and Fluoroscein Angiography Aggreement in Assessing Retinal Nonperfusion Area - Kurniawan Chalid; Iskandar Erwin; Rini Mayang (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2015)
Background: Retinal nonperfusion area assessment in retinal vein occlusion (RVO) patient is valuable to evaluate progression, therapy, and prognosis. Noninvasive method such as red free fundus photograph that has been processed using a specific program are expected to have correspondence with fundus fluorescein angiography (FFA), as the gold standard in assessing nonperfusion area. Methods: A cross-sectional study. 24 pairs of red free image and FFA were collected from RVO patients at Cicendo Eye Hospital selective consecutively admission from March until August 2013. Red free digital image processing was done by a technician and nonperfusion area was deliminated by a vitreoretina expert. Statistical analysis Wilcoxon signed ranks test was used to compared the nonperfusion area, Spearman correlation test to assessed the correlation coefficient, and the overlapping ratio was used to assessed the morphology suitability between two method. Results: Nonperfusion area analysis between two method showed no statistical difference (Zw 4.257, p=0.161, Wilcoxon) and have a high correlation(r>0.988, p=0.000, Spearman). Suitability was determined by the ratio of morphology overlap that approaches one (overlapping ratio was 0.89). Conclusion: Red free fundus photograph digital image processing has compatibility with the FFA in assessing nonperfusion area. It’s a noninvasive method, easy, safe, and can be used as an alternative for assessing nonperfusion area of RVO patients. Keywords: Nonperfusion area, red free fundus photograph, FFA, retinal vein occlusion